1991
DOI: 10.1111/j.1365-2249.1991.tb05597.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell proliferative responses to molecular fractions of periodontopathic bacteria

Abstract: SUMMARYSoluble antigenic preparations of Veillonella parvula and Bacteroides gingivalis were separated by SDS-PAGE and used after electroblotting and solubilization for in vitro lymphocyte stimulation in 13 patients with severe periodontitis and 12 controls. The cellular responses of controls and patients to V. parvula antigens were represented by four main proliferation-inducing fractions with 74-66, 52-46, 22-19 and 12 kD mol, wt. These fractions induced slightly enhanced DNA synthesis in lymphocytes from ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The literature 4–14 contains numerous contradictions with respect to T‐cell responses of patients with periodontitis. These contradictions may be due to differences in selected patient groups and the use of a great variety of experimental models and methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature 4–14 contains numerous contradictions with respect to T‐cell responses of patients with periodontitis. These contradictions may be due to differences in selected patient groups and the use of a great variety of experimental models and methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of subsequent studies have been contradictory. Some investigators 5–10 confirmed an association between AgP and a compromised proliferative activity of mononuclear cells (MNCs), whereas other investigators 11–14 found no such connection.…”
mentioning
confidence: 99%
“…In germ-free mice and rats, it was demonstrated that periodontal disease and caries, similarly to other human inflammatory diseases, cannot be experimentally induced in the absence of microbiota ( Heijl et al, 1980 ; Tlaskalova-Hogenova et al, 2004 ). Experimental animal models (e.g., the gavage model of periodontal disease) and in vitro studies revealed that certain components of oral microbiota, mainly P. gingivalis , play a crucial role in the innate host defense of periodontium and that dysregulation of the immune response in the presence of oral microbiota leads to inflammation and alveolar bone loss ( Ivanyi et al, 1991 ; Darveau et al, 2012 ; Papadopoulos et al, 2013 ). The mechanisms by which microbiota triggers the pathological changes are not yet fully understood, however, new approaches promise to shed light on the role of oral microbiota ( Kinane et al, 2017 ; Pitts et al, 2017 ).…”
Section: Oral Microbiome and Oral Diseasesmentioning
confidence: 99%